Corporate Social Performance, Legitimacy, and the Choice of Foreign Partners by State‐Controlled Entities in the Global Extractive Industries - Symeou, Pavlos C.; Kassinis, George I. (My University, 2023)
Partner selection in IJVs is an important but understudied phenomenon, especially when viewed from the perspective of the host country partner involved (Nippa and Reuer, 2019; Sun et al., 2021a). Contrary to the existing research’s assumption that international strategy decisions reflect the interests of MNEs, other organizations’ interests may be equally salient (Nippa and Reuer, 2019). Understanding the perspective of the host partner, the focus of this paper, is critical because, often, it is this local actor that initiates the search for foreign partners (Shi et al., 2014), or it can domi nate the partnership due to location specific advantages (Erramilli et al., 1997). Also, the value of nonmarket strategies, including managing CSP, aimed to give MNEs a foothold in the country (Sun et al., 2021b) hinges on the local partners’ perceptions. The host country partner perspective is especially salient when the local state is that partner and when one considers SCEs’ significant involvement in partnerships with MNEs (Sun et al., 2021a). SCEs often dominate their focal industries, exhibit unique i nstitutional logics, and play a mixed role as regulators, commercial enterprises, and social contributors. Importantly, they are unique in how their sociopolitical legitimacy is formed. This uniqueness stems mostly from the social contract between the stat e and the local society and from the state’s distinct salient sociopolitical stakeholders. The sociopolitical legitimacy of the state and its actors has significant implications for the success of the state’s economic exchanges with foreign MNEs. We draw on neo institutional theory (Kostova and Zaheer, 1999) and argue that in selecting an IJV partner, in addition to using other important task or partner related selection criteria, an SCE will evaluate partner characteristics that help enhance its legitima cy, that of the IJV, and ultimately that of the state in the eyes of salient stakeholders. One such characteristic is, as we posit, a candidate foreign partner’s CSP. We consider the legitimation mechanisms bolstered by CSP and explain how particular insti tutional factors in the foreign country, the host country, and supranationally interact with them, influencing CSP’s importance as a selection criterion. The context of our study is the global extractive industries. They are a crucial wealth creating instr ument for resource rich countries, which often rely on foreign partners to exploit resources. Because of the often disruptive effects of these industries’ activities on communities and the natural environment and local and international sociopolitical stak eholders’ scrutiny, the foreign partner’s CSP, the legitimacy of the IJV, and ultimately that of the SCE and the state may determine partnership success. We test our hypotheses using a sample of IJVs between SCEs from 48 countries and 203 foreign partners from 22 countries between 2000 2015. Our findings suggest that an MNE’s CSP can be an attractive selection criterion for an SCE because of its legitimacy effects. The SCE’s evaluation of CSP as legitimacy enhancing is influenced by the level of corruption in the MNE’s home country, the legiti macy of the host state, and the number of neighboring countries participating in international multi stakeholder initiatives. Our examination represents the first, to our knowledge, attempt to study the host state’s perspective in forming partnerships with foreign MNEs, considering MNEs’ CSP as a selection criterion, and showing how nonmarket strategy interacts with institutional elements at the host, home, and supranational levels.
Keywords: Corporate social performance; Extractive industries; International joint ventures; Legitimacy; State-controlled entities